English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-26 14:27:51 · 4 answers · asked by Olivia 4 in Science & Mathematics Mathematics

4 answers

Let u= sin2x , then du = 2cos2x dx

So the quation is now (e^u)/2 du

You can factor out the 1/2 to leave the integral of e^u du which is e^u + c

then redistribute the 1/2 to leave e^u + c/2 , but c/2 is any constant, so it becomes just .5e^u + c.

Substitute sin 2x back for u.

The answer is: .5e^(sin2x) + c

2006-10-26 14:37:33 · answer #1 · answered by Nobody 3 · 0 1

use substitution
u=sin2x
du=2cos2x dx

antiderivative of (cos 2x)e^sin2x
=integral of (cos 2x)e^sin2x dx
= integral of1/2 e^u du
=1/2 e^u+C
=1/2 e^sin2x + C

2006-10-26 21:29:43 · answer #2 · answered by locuaz 7 · 0 2

Let u = sin2x Therefore du/dx = 2 cos2x ie du = 2 cos2x dx

Integral(cos 2x)e^sin2x dx
= Integral e^sin2x . cos2x dx
= ½Integral e^sin2x . 2cos2x dx
= ½Integral e^u du
= ½ e^u + c
= ½ e^sin2x + c

2006-10-26 21:35:35 · answer #3 · answered by Wal C 6 · 0 1

let u = sin(2x) then du/dx = 2cos(2x)

then we have cos(2x) (e^u) du/[2cos(2x)

= (1/2)e^u du -------integrate to 1/2 e^(sin(2x)) + C

please check for errors

2006-10-26 21:33:24 · answer #4 · answered by Anonymous · 1 2

fedest.com, questions and answers